Adsorption of Nutrients from Stormwater Using Sawdust - Harmayani, Kadek; Anwar, Faisal (International Association of Computer Science and Information Technology (IACSIT), 2012)
This study investigates the adsorption characteristics of sawdust for removing nutrients (e.g., NH3-N,NO3-N, and NO2-N) from stormwater. A series of laboratory batch experiments was performed and the effects of different parameters on nutrient adsorption were observed. The parameters of concern include: initial concentration (0.5-5mg/L) and dosage (2-20mg of dry sawdust). Results revealed that themaximum removal was obtained at lower initial concentration. An increase of adsorbent dosage increased the percent removal of NH3-N, NO3-N, and NO2-N. The maximum removal of NO3-N,and NO2-N was found 100%, while NH3-N removal was found 55%. The sorption of sawdust was characterized by Langmuir and Freundlich isotherm and the results show that the correlation coefficient of applicability (R2) of Freundlich model (R2 = 0.8324, 0.9856, and 0.9231 for NH3-N, NO3-N and NO2-Nrespectively) fits better than Langmuir (R2 = 0.7963, 0.9751, and 0.8049 for NH3-N, NO3-N and NO2-N respectively).